Perancangan Media Pembelajaran Interaktif Adobe Animate CC Desain Komunikasi Visual Kelas XI SMK - Dastri, Dean Oksaputra; Sefriani, Rini; Radyuli, Popi (Bitnet: Jurnal Pendidikan Teknologi Informasi, 2025)
This study aims to design and develop an interactive learning medium using Adobe Animate CC as a teaching tool for the Visual Communication Design subject for Grade XI students at SMK N 3 Padang. The lack of engaging and effective interactive learning media, along with predominantly one-way evaluation methods, forms the basis for the development of this medium. The research adopts a Research and Development (R&D) approach using the ADDIE development model, which includes Analyze, Design, Development, Implementation, and Evaluation stages. Validation results from three experts indicate that the media is highly valid, with an average score of 89.33%. Student assessments of practicality place the media in the highly practical category 88.14%, and its effectiveness in the learning process is rated as highly effective 87.53%. This interactive learning medium is designed to provide a more engaging and enjoyable learning experience through instructional content and quizzes aligned with the Visual Communication Design curriculum.